Epigenetic control of a VDR-governed feed-forward loop that regulates p21((waf1/cip1)) expression and function in non-malignant prostate cells - Thorne, James L. (Oxford University Press, 2011)
In non-malignant RWPE-1 prostate epithelial cells signaling by the nuclear receptor Vitamin D Receptor (VDR, NR1I1) induces cell cycle arrest through targets including CDKN1A (encodes p21((waf1/cip1))). VDR dynamically induced individual histone modification patterns at three VDR binding sites (R1, 2, 3) on the CDKN1A promoter. The magnitude of these modifications was specific to each phase of the cell cycle. For example, H3K9ac enrichment occurred rapidly only at R2, whereas parallel accumulation of H3K27me3 occurred at R1; these events were significantly enriched in G(1) and S phase cells, respectively. The epigenetic events appeared to allow VDR actions to combine with p53 to enhance p21((waf1/cip1)) activation further. In parallel, VDR binding to the MCM7 gene induced H3K9ac enrichment associated with rapid mRNA up-regulation to generate miR-106b and consequently regulate p21((waf1/cip1)) expression. We conclude that VDR binding site- and promoter-specific patterns of histone modifications combine with miRNA co-regulation to form a VDR-regulated feed-forward loop to control p21((waf1/cip1)) expression and cell cycle arrest. Dissection of this feed-forward loop in a non-malignant prostate cell system illuminates mechanisms of sensitivity and therefore possible resistance in prostate and other VDR responsive cancers.